The Influence of Work Engagement and Work Environment on Employee Performance Through Job Satisfaction at PT. Kiat Ananda Group In Surabaya - Karno; Tri Kartika Pertiwi; Ika Korika Swastika (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the effect of work engagement on employee performance, to analyze the effect of work environment on employee performance, to analyze the effect of work engagement on employee performance through job satisfaction, and to analyze the effect of work environment on employee performance through job satisfaction. The research method uses a quantitative approach with the population consisting of all employees of PT. Kiat Ananda Group, totaling 80 people. The sample for this study used a census technique, where the entire population was included as the sample. Data processing and analysis were performed using the Partial Least Square (PLS) method with the SmartPLS 3.0 software to test the relationships between variables. The results indicate that work engagement and work environment have a positive effect on employee performance. Moreover, job satisfaction was found to significantly mediate the effects of work engagement and work environment on employee performance. These findings suggest that improving employee performance can be achieved through enhancing work engagement and a conducive work environment, supported by high levels of job satisfaction